SISTEM INFORMASI PEMINJAMAN BUKU PERPUSTAKAAN DI SEKOLAH BERBASIS CLIENT SERVER - Daniel Adi Putranto; Siska Ratnasari (Pusat Riset dan Inovasi Nasional, 2021)
In the current era of globalization, computer users are increasing. Almost every job in school institutions uses computer aids as well as in SMP N 1 Salatiga which is located on Jl. R. Soeprapto No. 34 really need to use a computer. Especially in the school library which has not been able to take advantage of the sophistication of computer technology in recording school tuition payments. The problem that is often encountered is that in the data processing process errors are still found at the time of recording in making SPP payment transactions because they are still processed manually by being recorded in the books one by one so that the resulting calculation of school tuition payments is less accurate. With these problems the author tries to formulate a problem, namely how to make a computerized program for paying school tuition and using a multiuser-based program at SMP N 1 Salatiga in order to process data more quickly with a minimum error rate. In making this thesis, the author uses Visual Basic 6.0 software and the data base uses Microsoft Access.